Echocardiographic Findings in Chronic Obstructive Pulmonary Disease Patients - Khatri, Devendra; Karki, Parag; Shrestha, Dhan Bahadur; Khatri, Rishi; Thapa, Raj Kumar; Panta, Chiranjibi; Budhathoki, Lee (Birat Journal of Health Sciences, 2018)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is parenchymal lung disease with systemic effects and hemodynamic alteration more so in pulmonary circulation. In COPD, right ventricular (RV) after load increases due to structural and mechanical changes in the pulmonary vascular bed leading to increase in pulmonary arterial pressure which also leads to alteration in structure and function of RV. In COPD, congestive cardiac failure and ventricular dysfunction may coexist and demands proper assessment and management of dual condition. Objectives: This study was aimed to study the effect of COPD in cardiac anatomical and functional parameters in COPD patients in Shree Birendra Hospital. Methodology: This study was a retrospective review of hospital data on echocardiographic findings in 86 COPD patients visiting the outpatient department (OPD) in six months from June 2016 to December 2016. Available data was entered, edited and analyzed using Statistical package for social sciences (SPSS) version 22. Results: Among 86 cases studied, 43% had dilated RA and 41% with dilated RV, 24% with dilated LA and dilated LV in 22%. Normal pulmonary artery pressure was present in 41 (48%) cases and 45(52 %) individuals were having PAH. Among valvular disorder tricuspid regurgitation was commonest (50%). Left ventricle abnormalities like dilated left ventricles, LVDD, concentric ventricular hypertrophy, LVSD were also presented in significant number of COPD patients counting 22%, 37%, 7%, 30% respectively. Among the various factors analyzed in echocardiogram; there was significant association between the PAH with right atrial dilatation, right ventricular dilatation, left atrial dilatation, LVDD, tricuspid regurgitation (p<0.05) while rest of the parameters were not statistically significant association. Conclusion: COPD in most instances associated with some form of cardiac abnormalities like PAH, LVDD, LVSD, TR, dilated cardiac chambers so echocardiographic evaluation in timely basis has pivotal role in COPD cases to detect hemodynamic and mechanical alterations. BJHS 2018;3(1)5 : 342-345